Decision analysis for managers : a guide for making better personal and business decisions - Charlesworth, David (2013 digital library., 2013)
Everybody has to make decisions--they are unavoidable. Yet we receive little or no education or training on how to make decisions. Business decisions can be difficult: which people to hire, which product lines or facilities to expand and which to sell or shut down, which bid or proposal to accept, which process to implement, how much R & D to invest in, which environmental projects should receive the highest priority, and so on. Even if you make the correct decision, you still have to get buy-in and commitment from your team, other management, and key stakeholders to successfully implement the decision. Personal decisions can be even more difficult: which college to attend, who to date, who to marry, which automobile to buy, which house to buy, whether to change jobs or not, where to go on vacation, when and where to retire, how to handle and treat a serious illness or health problem, and so on. Decision analysis (DA) is a time-tested set of tools (mental frameworks) which will help you and the teams you work with clarify and reach alignment on goals and objectives and understand trade-offs in reaching those goals, develop and examine alternatives, systematically analyze the effects of risk and uncertainty, and maximize the chances of achieving your goals and objectives.